2016
DOI: 10.14709/barbj.9.1.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of bat diversity in the Taita Hills Afromontane cloud forests, southeastern Kenya

Abstract: Tropical mountain ranges are known to support high biodiversity. In addition to their role as refuge habitat, complex topography within these ecosystems promotes the development of diverse species traits and evolutionary divergence. However, species within these environments also face severe anthropological threats, most notably from habitat loss and degradation, invasive species, and climate change. A primary example is the Taita Hills in Kenya, which forms the northernmost portion of the biodiversity rich Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Urbanization has dramatically increased over recent decades in Taita-Taveta County, with over 95% of original forest cover cleared and a 700% increase in development landcover [ 34 , 35 ]. Bat diversity is high here, with over 30 species recorded in the county [ 36 ] and humans often have bats living in their buildings (electronic supplementary material, figure S2). The region has also been identified as a hotspot for zoonotic disease emergence and numerous bat species in the area are known to host a diversity of pathogens [ 27 , 28 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Urbanization has dramatically increased over recent decades in Taita-Taveta County, with over 95% of original forest cover cleared and a 700% increase in development landcover [ 34 , 35 ]. Bat diversity is high here, with over 30 species recorded in the county [ 36 ] and humans often have bats living in their buildings (electronic supplementary material, figure S2). The region has also been identified as a hotspot for zoonotic disease emergence and numerous bat species in the area are known to host a diversity of pathogens [ 27 , 28 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…and Vespertilionidae (Vesper bats, 36 spp.). While several ecological studies have been undertaken on bats in Kenya (McWilliam 1987, Webala et al 2004, Wechuli et al 2016, López-Baucells et al 2016, the absence of specific country bat call libraries in Africa which document calls of local bat species limits accurate identification of calls from acoustic detectors (Monadjem et al 2017). Although none of the previous bat studies in Kenya were on bat activity, two (Webala et al 2004, Wechuli et al 2016 which concomitantly investigated bat diversity in protected areas and agricultural landscapes, showed that the farmlands had low species richness as compared to the protected areas.…”
Section: Introductionmentioning
confidence: 99%